Increasing the Mathematics Learning Through the Development of Vocational Mathematics Modules of STKIP Muhammadiyah Enrekang - Suarti Djafar; Nadar Nadar; Arwan Arwan; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2019)
This research is Classroom Action Research which will be carried out in two cycles and through several stages in each cycle, namely planning, implementing actions, observing and reflecting. The purpose of this study was to determine the increase in mathematics learning outcomes of STKIP Muhammadiyah Enrekang students through the development of vocational mathematics modules. The subjects of this study were the fourth semester students of the 2018/2019 academic year study program in mathematics, totaling 10 people. The data collection technique that will be used is a test of student learning outcomes conducted at the end of each cycle, observation, reflection and student responses. The implementation plan begins with asking questions, thinking together and answering; 2) Application of the development of vocational mathematics modules about improving the learning outcomes of the mathematics education study program STKIP Muhammadiyah Enrekang. The goals and objectives of education held at the mathematics education study program of STKIP Muhammadiyah Enrekang can be achieved well, in order to produce vocational math modules for mathematics education study programs.